Reproductive, productive and financial consequences of chronic Trypanosoma vivax infection in a dairy cattle herd in a region without a cyclic vector - Couto, Luiz Fellipe Monteiro; Bastos, Thiago Souza Azeredo; Morais, Igor Maciel Lopes de; Salvador, Vanessa Ferreira; Leal, Luccas Lourenzzo Lima Lins; Falavigna, Ricardo Backstron; Spricigo, José Felipe Warmling; Mota, Rinaldo Aparecido; Cruz, Breno Cayero [UNESP]; Colli, Marcos Henrique Alcantara; Scarpa, Alexandre Braga; Soares, Vando Edesio; et al. (Elsevier, 2024)
This study evaluated the reproductive, productive and financial consequences of chronic Trypanosoma vivax infection in a dairy cattle herd located in a region without the cyclic vector during two years. Animals were categorized as either positive (chronically infected) or negative for T. vivax antibodies using a commercial rapid test. Additionally, serum samples from cows were analyzed for the presence of anti-Neospora caninum antibodies. Pregnancy diagnoses were performed through rectal palpation and ultrasonography after 30, 60 and every 21 days until the 144th day of pregnancy. If an abortion occurred in the final trimester, serology and cPCR were performed on calves for T. vivax and N. caninum. The breeding period, calving interval and pregnancy losses were recorded. The milk production of each animal during the 305 days of lactation was measured, and the annual financial impact of milk production was calculated using a revenue minus feed cost (RMFC) indicator. Out of 177 cows, 71.75 % were chronically infected, and 13.50 % were T. vivax-negative. No correlation (p = 0.8854) of co-infection between T. vivax and N. caninum was observed. Negative cows required fewer (p≤0.05) artificial inseminations than chronically infected ones. T. vivax was not significantly associated (p = 0.7893) with pregnancy loss up to 81 days of pregnancy. Cows chronically infected by T. vivax had 4-fold greater chance (p = 0.0280) of experiencing pregnancy loss between 82 and 144 days of gestation. Eighteen cows aborted, two were positive for T. vivax antibodies, and one for N. caninum antibodies. The calves were negative for T. vivax and N. caninum. Chronically infected cows and negative cows for T. vivax that experienced pregnancy loss (82–144 days of pregnancy) had a longer (p≤0.05) breeding period to become pregnant, and consequently a longer calving interval compared to cows that maintained pregnancy. The difference (p≤0.05) in milk production was evident when pregnancy loss occurred between 82 and 144 days of gestation in cows chronically infected by T. vivax. The RMFC indicated a negative impact of 38.2 % on the farm's annual milk revenue due to the presence of chronically infected cows.
Keywords: Milk production; Pregnancy loss; Revenue minus feed cost; Trypanosomosis